2019
DOI: 10.1002/cyto.a.23937
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Multiphoton Imaging of the Bone and Bone Marrow Environment

Abstract: Over the last two decades, numerous advances in our understanding of bone cell biology and bone mineral homeostasis have been achieved. As a dynamic connective and supportive tissue, bone is constantly sensing and responding to both external mechanical forces and internal systemic and local signals. A variety of intravital imaging approaches have been investigated to identify molecular and cellular processes and to decipher signaling pathways involved in the cellular communication between different types of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…The consequences of these forces on haematopoiesis are beginning to emerge. For instance, it has been shown that hydrostatic pressure improves the clonogenic potential and CD34+ cell number in ex-vivo cultures (Kim and Bixel, 2020). PIEZO1 may be one of the sensors that could be involved in perceiving these forces and integrating them into a cellular response, for instance through integrin activation as shown here.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The consequences of these forces on haematopoiesis are beginning to emerge. For instance, it has been shown that hydrostatic pressure improves the clonogenic potential and CD34+ cell number in ex-vivo cultures (Kim and Bixel, 2020). PIEZO1 may be one of the sensors that could be involved in perceiving these forces and integrating them into a cellular response, for instance through integrin activation as shown here.…”
Section: Discussionmentioning
confidence: 75%
“…The semi-solid bone marrow is occupied with a heterogeneous pool of cells that will perceive and induce particular cellular programs upon shear forces from fluid movements, tensile strain, hydrostatic pressure and other physical forces (Meyer et al, 2016;Kim and Bixel, 2020). The consequences of these forces on haematopoiesis are beginning to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the bone marrow is the natural reservoir of MSCs. These cells maintain a stable bone mass and then bone homeostasis through life by differentiating to the osteoblastic lineage, able to secrete bone matrix [ 13 , 33 , 40 ]. Beside it, MSCs can differentiate into the chondrogenic and adipogenic lineages [ 3 ].…”
Section: Immunity: a Pivotal Player To Achieve And Maintain Osseointementioning
confidence: 99%
“…These interactions include heterogeneous cell populations (immune cells, bone, and vascular cells) [ 10 , 11 ]. The specific interaction between immune and bone cells is called the “osteoimmune system” [ [12] , [13] , [14] , [15] ]. In turn, osteoimmunology has become a fundamental discipline for the study of several inflammatory diseases, the crosstalk between bone and the immune system, and the influence of the immune system on bone regeneration and consumption [ 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are only limited areas where this imaging can be applied. However, the recently developed three-photon microscopy substantially improves the penetration depth and is expected to overcome these limitations with its resolution [ 35 ]. Moreover, because of the wide scattering of light, it is difficult to visualize inflamed tissues with effusion or tissues with bleeding using multiphoton microscopy.…”
Section: Introductionmentioning
confidence: 99%